Integrating BioEnergi : Living Lab Renewable Energy TPST 3R Mulyoagung Sejahtera - Junus, Mochammad; Lukmana Putra, Indra; Risdiana, Devi Mega; Rifa’i, Muhamad; Syuliswati , Atika; Widhiyanti, Santi (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Integration of renewable energy systems based on biomass and biogas in the BioEnergi Living Lab project at TPST 3R Mulyoagung Bersatu. The primary aim is to develop an educational, research, and technology innovation space for renewable energy conversion through waste processing, particularly using biogas and biomass-based technologies. Background Problems: Urban waste management issues require innovative solutions, particularly in the application of 3R (Reduce, Reuse, Recycle) principles. The potential for converting organic waste into renewable energy offers significant benefits, including reducing fossil fuel dependency and mitigating greenhouse gas emissions. Research Methods: BPMN-based modelling which employs a community-driven Living Lab model, integrating both technological innovation (such as biodigesters, pyrolysis, and IoT) and social engagement. Involves active collaboration between universities, local communities, and government agencies to implement and monitor renewable energy conversion technologies, data collection through IoT sensors and real-time monitoring systems. Finding/Results: Project successfully demonstrated the capacity of converting 15-30 tons of organic waste monthly using biodigesters and pyrolysis for up to 6 tons of plastic and 5 tons of paper. IoT-enabled systems ensured real-time monitoring of critical parameters such as gas production, reactor temperature, and safety protocols. Highlight the potential for creating a circular economy model by producing biogas, biochar, and organic fertilizers.. Conclusion: BioEnergi Living Lab project offers a sustainable and scalable model for waste-to-energy conversion, contributing to both energy independence and environmental sustainability. Innovative addresses urban waste management issues, community engagement and local economic growth through renewable energy-based solutions._